2019
DOI: 10.1016/j.jsxm.2019.11.264
|View full text |Cite
|
Sign up to set email alerts
|

Is Mode of Delivery Associated With Sexual Response? A Pilot Study of Genital and Subjective Sexual Arousal in Primiparous Women With Vaginal or Cesarean Section Births

Abstract: Introduction: Although postpartum sexual concerns are common, limited data exist on postpartum sexual response. Furthermore, the physiological process of vaginal birth may negatively impact genital response compared with unlabored cesarean section (C-section), but this hypothesis has yet to be tested. Aim: To (i) compare genital and subjective sexual response and sexual concordance by mode of delivery with inclusion of a control group, (ii) compare groups on self-reported sexual function over the past month, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
(72 reference statements)
1
5
0
1
Order By: Relevance
“…With respect to the effect of delivery type on the sexual function, there was no statistically significant difference between cesarean and vaginal delivery in 10 studies [ 12 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Among the remaining six studies, one found no statistically significant difference between groups apart from the arousal subscale [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the effect of delivery type on the sexual function, there was no statistically significant difference between cesarean and vaginal delivery in 10 studies [ 12 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Among the remaining six studies, one found no statistically significant difference between groups apart from the arousal subscale [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a case-control study to analyze the genital response in the postpartum period, it was observed that women with vaginal delivery had decreased genital flow compared to women undergoing caesarean delivery. However, both groups did not present significant differences regarding subjective sexual experience 47 .…”
Section: Sociocultural Aspectsmentioning
confidence: 67%
“…Laser Doppler flowmetry data were collected at a highly localized area on the labia minora and results from this study may have differed if the laser had been placed on a different area of the vulva, or if the laser placement was inconsistent across experimental stimuli due to participant movement. However, genital responses assessed by laser Doppler flowmetry exhibited high correlations with blood flow assessed using the laser Doppler imager within testing sessions (r(43) = .73, p < .001) and across (r(35) = .62, p < .001), suggesting that data obtained by single-point measurement were consistent with the conventional approach of assessing blood flow in a larger region of interest (Bouchard et al, 2017;Boyer et al, 2012Boyer et al, , 2013Cappell et al, 2020;Waxman & Pukall, 2009). With respect to potential variability in laser placement across the testing session, consistency was attained by emphasizing to participants the importance of remaining still during testing and providing support to the legs and buttocks with pillows to limit movement.…”
Section: Limitations and Future Directionsmentioning
confidence: 77%
“…Additional research showed that the laser Doppler imager is a specific measure of women's genital response, detecting increases in genital blood flow for sexual, but not neutral or emotionally evocative, nonsexual stimuli (e.g., anxiety, humor; Waxman & Pukall, 2009) and is sensitive to varying degrees of genital response elicited by stimuli of different sexual intensities (Bouchard et al, 2019). Laser Doppler imaging also distinguishes the genital response patterns of women with and without a genito-pelvic pain disorder (i.e., provoked vestibulodynia; Boyer et al, 2013), as well as women who have given birth vaginally compared to those who have not given birth (Cappell et al, 2020). Furthermore, genital blood flow assessed via laser Doppler imaging has been shown to exhibit a moderate, positive correlation with an objective measure of genital lubrication (Bouchard et al, 2019), which is a theoretically-related aspect of sexual response (Levin, 2003).…”
Section: Laser Doppler Imaging Of Genital Responsementioning
confidence: 99%
See 1 more Smart Citation